A conditionally heteroskedastic global inflation model - Leonardo Morales-Arias; Guilherme V. Moura (Kiel Institute for the World Economy (IfW), 2010)
This article proposes a multivariate model of inflation with conditionally heteroskedastic common and country-specific components. The model is estimated in one-step via Quasi-Maximum Likelihood for the G7 countries for the period Q1-1960 to Q4-2009. It is found that various model specifications considered fit well the first and second order dynamics of inflation in the G7. The estimated volatility of the common inflation component captures the international effects of the 'Great Moderation' and of the 'Great Recession'. The model also shows promising capabilities for forecasting inflation in several countries.
Keywords: E31; E37; F41; 330; global inflation; conditional heteroskedasticity; inflation forecasting; Inflation; Prognoseverfahren; Heteroskedastizität; Multivariate Analyse; Maximum-Likelihood-Methode; Schätzung; G-7-Staaten